Negotiating transgender identity and well-being in Javanese Muslim contexts: Religiosity and social support - Rr. Siti Kurnia Widiastuti (Priviet Social Sciences Journal, 2026)
This study examines how religiosity and social support shape the identities and impact the well-being of transgender people in Javanese Muslim society. This research uses a qualitative approach and employs in-depth interviews, focus group discussions, direct observations, and documentation within transgender communities in Yogyakarta and Central Java. This study included 11 transgender individuals from Yogyakarta and Central Java. The study reveals that transgender identity is formed through adaptation and negotiation within families, schools, social circles, and religious communities. Family and community support are key to maintaining mental health and social relationships, whereas limited gender norms and strongly held religious views restrict the social space for transgender people. This study stresses that the well-being of transgender people is not only affected by psychological and economic factors but also by positive social acceptance and access to inclusive places of worship. These results contribute to an integrative understanding of gender, religiosity, and social support within the Javanese socio-religious context.